Content: Evolution & Development 2/2016. Issue 2 (March 2016) - Unknown
Abstract : Cover image: Soldier of Nasutitermes takasagoensis (Isoptera: Termitidae), and micro computed tomography of the head showing a frontal gland enveloped by inflated muscles.